Supportive Peer Feedback in Tertiary Education: Analysis of Pre-Service Teachers' Perceptions - Dolors Cañabate; Lluís Nogué; Teresa Serra; Jordi Colomer (MDPI AG, 2019)
To acquire knowledge about student-mediated peer-to-peer collaborative activities, pre-service teachers' perceptions of peer feedback are analyzed and categorized as receiver, provider, or cognitive feedback. A questionnaire of 15 survey questions concerning supportive feedback from peers was designed and validated using assessments from more than 200 pre-service teachers. The questionnaire was aligned with the activities promoting supportive feedback between pre-service teachers from three bachelor's degrees at a tertiary education institution. Their perceptions were then quantified in terms of the peer feedback categories. While there were significant correlations between the scores for all 15 questions, real insights were produced when the highest correlations were analyzed. As such, being involved as both feedback providers and receivers was highly rated. The self-efficacy of pre-service teachers receiving feedback, (i.e., the extent to which peer instructional strategies and the selected learning tasks were cognitively challenging so as to improve receiver feedback), proved to be correlated with their perceptions of involvement, autonomy, and structure. Likewise, motivation for providing or receiving feedback was also closely correlated with the self-efficacy of pre-service teachers providing feedback. Finally, all three questions in the cognitive feedback category were highly correlated. The pre-service teachers were, thus, motivated to improve their learning and considered feedback as a useful task and as a way to strengthen their relationships with their peers.